Inheritance of fields of study - Adam Altmejd (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2023)
University graduates are more than three times as likely to hold a degree in the field that their parent graduated from. To estimate how much of this association is caused by the educational choices of parents, I exploit admission thresholds to university programs in a regression discontinuity design. I study individuals who applied to Swedish universities between 1977 and 1992 and evaluate how their enrollment in different fields of study increases the probability that their children later study the same topic. I find strong causal influence. At the aggregate level, children become 50% more likely to graduate from a field if their parent has previously enrolled in it. The effect is positive for most fields, but varies substantially in size. Technology, engineering, medicine, business exhibit the largest, significant, effects. For these fields, parental enrollment increases child graduation probability with between 2.0 and 12.8 percentage points. I show that the parent's labor market experience plays an important role in explaining the results, but parental field enrollment does not increase subject-specific skills, nor is it associated with higher returns to earnings. I find little evidence for comparative advantage being the key driver of field inheritance. Rather, parents seem to function as role models, making their own field choice salient. This is indicated by the fact that children become less likely to follow parents with weak labor market prospects, and that children are more likely to follow the parent with the same gender.
Keywords: I24; J62; 330; intergenerational transmission; fields of study